Behavioral Modeling dalam Pemilihan Moda Transportasi Melalui Analisis Preferensi Pengguna terhadap Bus Trans Jatim Rute Lamongan–Mojokerto - Nur Indah Mukhoyyaroh; Ardi Ansyah; Dwi Kartikasari (Jurnal Talenta Sipil, 2026)
Effective public transportation is essential for reducing society's dependence on private vehicles and promoting sustainable mobility. The implementation of the Trans Jatim Bus service on the Lamongan–Mojokerto route is expected to provide a more efficient transportation alternative; however, the level of modal shift among the community still requires further investigation. This study aims to analyze the factors influencing people's decisions to shift to the Trans Jatim Bus and to determine the probability of modal shift occurrence. This research employed a quantitative approach through a questionnaire survey involving 100 respondents selected using purposive sampling. The collected data were analyzed using binary logistic regression to identify variables that significantly affect the decision to shift transportation modes. The results indicate that gender and travel frequency significantly influence modal shift decisions, with significance values of 0.031 and 0.047, respectively. The highest probability of modal shift was found among male respondents at 82.4%, while respondents who traveled daily showed a modal shift probability of 55.6%. These findings suggest that user characteristics and travel intensity play important roles in encouraging the use of public transportation. Therefore, improving service quality, particularly in terms of travel frequency, should become a priority for operators and government authorities to increase public interest in using the Trans Jatim Bus service.